Targeting mutation sites in the omicron variant of SARS-CoV-2 as potential therapeutic strategy against COVID-19 by antiretroviral drugs - Ochuko L. Erukainure; Aliyu Muhammad; Rahul Ravichandran; Musa M. Abarshi; Sanusi B. Katsayal; Murtala B. Abubakar; Ya'qub U. Abiodun; Olubunmi Atolani; Robert Preissner; Priyanka Banerjee (Toxicology Reports)
The multiple mutation of the spike (S) protein of the Omicron SARS-CoV-2 variant is a major concern, as it has been implicated in the severity of COVID-19 and its complications. These mutations have been attributed to COVID-19-infected immune-compromised individuals, with HIV patients being suspected to top the list. The present study investigated the mutation of the S protein of the omicron variant in comparison to the Delta and Wuhan variants. It also investigated the molecular interactions of antiretroviral drugs (ARVd) vis-à-vis dolutegravir, lamivudine, tenofovir-disoproxilfumarate and lenacapavir with the initiation and termination codons of the mRNAs of the mutated proteins of the omicron variant using computational tools. The complete genome sequences of the respective S proteins for omicron (OM066778.1), Delta (OK091006.1) and Wuhan (NC 045512.2) SARS-CoV-2 variants were retrieved from the National Center for Biotechnology Information (NCBI) database. Evolutionary analysis revealed high trends of mutations in the S protein of the omicron SARS-CoV-2 variant compared to the delta and Wuhan variants coupled with 68 % homology. The sequences of the translation initiation sites (TISs), translation termination sites (TTSs), high mutation region-1 (HMR1) and high region mutation-2 (HMR2) mRNAs were retrieved from the full genome of the omicron variant S protein. Molecular docking analysis revealed strong molecular interactions of ARVd with TISs, TTSs, HMR1 and HMR2 of the S protein mRNA. These results indicate mutations in the S protein of the Omicron SARS-CoV-2 variant compared to the Delta and Wuhan variants. These mutation points may present new therapeutic targets for COVID-19.